Fatal Errors: The Mortality Value of Accurate Weather Forecasts - Jeffrey G. Shrader; Laura Bakkensen; Derek Lemoine (Institute of Labor Economics (IZA), 2023)
We provide the first revealed preference estimates of the benefits of routine weather forecasts. The benefits come from how people use advance information to reduce mortality from heat and cold. Theoretically, more accurate forecasts reduce mortality if and only if mortality risk is convex in forecast errors. We test for such convexity using data on the universe of mortality events and weather forecasts for a twelve-year period in the U.S. Results show that erroneously mild forecasts increase mortality whereas erroneously extreme forecasts do not reduce mortality. Making forecasts 50% more accurate would save 2,200 lives per year. The public would be willing to pay 112 billion to make forecasts 50% more accurate over the remainder of the century, of which 22 billion reflects how forecasts facilitate adaptation to climate change.
Keywords: D83; I12; Q51; 330; weather forecasts; information provision; mortality; climate change